IDENTIFYING THERMAL COMFORT OF TROPICAL ARCHITECTURAL CONCEPT BUILDING : A CASE STUDY OF EXPANDABLE HOUSE - Rickie Cung; Amanda Rosetia (Journal of Architectural Research and Education, 2023)
Tropical architecture is an architectural building concept that focuses on the use of materials and techniques used in an accordance with the environment and climate in the tropical region. Buildings with tropical architectural style have special characteristics in adapting to climate conditions, but currently there are also modern buildings that can be categorized as contemporer tropical buildings. In the context of Batam city, contemporer tropical architectural buildings have not been prominent, especially in residential houses applications. Moreover, few residential houses failed to follow thermal comfort in the objective of Batam climate. This study aims to identify the elements of thermal comfort in residential houses which apply contemporer tropical architectural concepts in the city of Batam. In this case the author examine â€œRumah Tambahâ€ as a case study. By conducting a literature review and comparison of case studies as well as direct observation to the location, this research was conducted using an inductive qualitative method using primary and secondary data. Finally, this research produces an identification of thermal comfort that is applied to residential houses with a contemporer tropical architectural concept and provides recommendations for design elements in residential houses with a contemporer tropical architectural concept in the city of Batam.Â